2015
DOI: 10.5114/pdia.2014.40960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psoriasis activity on serum adiponectin and leptin levels

Abstract: IntroductionPsoriasis is an inflammatory and chronic skin disease associated with obesity, cardiovascular diseases, diabetes and metabolic syndrome. Adipokines, as bioactive substances secreted from adipose tissue, are involved in various metabolic diseases.AimTo investigate the association between psoriasis severity and serum adiponectin and leptin levels in patients with psoriasis.Material and methodsSerum fasting adiponectin and leptin levels were examined by an enzyme-linked immunosorbent assay in 49 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
45
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 42 publications
(85 reference statements)
3
45
0
3
Order By: Relevance
“…Along these lines, TNF-α plasma concentration negatively and significantly correlated with plasma adiponectin levels, whereas plasma leptin levels were not correlated [57]. Conversely, in another study, both serum adiponectin and leptin levels were significantly decreased in psoriatic patients in comparison with the control group [58]. Other reports detected significantly lower levels of adiponectin and visfatin, and significantly higher levels of vaspin, omentin, chemerin, and resistin in psoriatic patients as compared to the control group [42, [59][60][61][62].…”
mentioning
confidence: 72%
“…Along these lines, TNF-α plasma concentration negatively and significantly correlated with plasma adiponectin levels, whereas plasma leptin levels were not correlated [57]. Conversely, in another study, both serum adiponectin and leptin levels were significantly decreased in psoriatic patients in comparison with the control group [58]. Other reports detected significantly lower levels of adiponectin and visfatin, and significantly higher levels of vaspin, omentin, chemerin, and resistin in psoriatic patients as compared to the control group [42, [59][60][61][62].…”
mentioning
confidence: 72%
“…Te ostatnie biorą udział w utrzymaniu homeostazy organizmu, regulacji metabolizmu węglowodanów i tłuszczów, hemostazy, rozwoju insulinooporności, miażdżycy oraz procesów zapalnych i immunologicznych. W licznych badaniach udowodniono rolę różnych adipokin w patogenezie łuszczycy w powiązaniu z chorobami ogólnoustro-jowymi [61][62][63][64].…”
Section: Obesityunclassified
“…The latter take part in maintaining systemic homeostasis, regulation of carbohydrate and lipid metabolism, haemostasis, insulin resistance, atherosclerosis, and inflammatory and immune processes. Numerous studies demonstrated the role of various adipokines in the pathogenesis of psoriasis in association with systemic diseases [61][62][63][64].…”
Section: Obesitymentioning
confidence: 99%
“…Various adipokines have been examined and previously published studies have reported their potential role in the development of certain diseases, such as diabetes, obesity, metabolic syndrome, systemic sclerosis and also psoriasis (6). Especially leptin, adiponectin, resistin or visfatin have been widely studied in patients with psoriasis and considered as linking this disease with its comorbidities (7)(8)(9)(10). Lipocalins belonging to adipokines have been of interest in various medical fields and psoriasis as well.…”
Section: Introductionmentioning
confidence: 99%